Design and fabricate welding machine cart - Zulfadli Adha, Nadzri (2012)
Designing and fabricating a welding machine cart for the welders is a product that fulfills the welder’s needs. This project uses many materials such as mild steel, galvanized iron, stainless steel and others. Overall, this project involves many processes, starting from the design concept, fabrication and assembling procedures. Even though there are many types of welding machine cart in the market, the completion of this new model provides a more practical usage.